PH Dependent Controlled Release of CTAB Incorporated Dipyridamole Drug from Agar-Based Hydrogel. (3rd March 2016) - Date, Pranjali; Ottoor, Divya
ABSTRACT: Highly pH sensitive hydrogels, based on agarose and acrylamide were synthesized and characterized by Fourier transform infrared spectroscopy, thermogravimetric analysis, differential scanning calorimeter, and scanning electron microscopy. The release of dipyridamole from the hydrogel matrix was monitored using fluorescence spectroscopy. Since the solubility of the drug gets enhanced by cationic surfactant, an inclusion complex was prepared using cetyl trimethylammonium bromide and the release of inclusion complex from the polymer matrix was also studied. Swelling behavior of the prepared hydrogels in different pH media were studied at room temperature and maximum swelling was observed at basic pH. GRAPHICAL ABSTRACT: